Peningkatan Ketrampilan Pengrajin Mebel Melalui Pelatihan Perancangan Produk dari Limbah Hasil Produksi - Arifin, Zaenal; Widiastuti, Nur Aeni; Zainudin, Achmad; Widodo, Agustina; Niamirroykhan, Achmad Syafiul; Najid, Muhammad Reza Ahsanun; Saputra, Reihan; Artalopa, Ryan (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Balikpapan (LPPM UNIBA), 2025)
Jepara Regency's leading products are carvings and furniture. These superior products are concentrated in Ngabul Village and Sukodono Village, Tahunan District, Jepara Regency. The partners in this service are Srijaya Indofurniture and I-Design Furniture which operates in the furniture sector and is already on an export scale. Even though partners have exported, they also experience several problems, one of which is the management aspect, namely: a) there are still difficulties in analyzing production planning so that a lot of raw materials are wasted and b) lack of partner knowledge in processing wood waste into products of marketable value. The methods used to overcome this problem are socialization of activities, training on processing furniture waste, mentoring, monitoring and evaluation of activities. The results of this activity are for partner employees to increase their knowledge in processing furniture waste into products with sales value and aesthetics.